Magnificence [large type] : a novel - Millet, Lydia, 1968- (Center Point Large Print, 2013)
After her husband's death, Susan Lindley moves into her late great-uncle's Pasadena mansion and restores his taxidermy collection while being joined in the residence by an equally strange human menagerie.